Evolutionary psychology and economic theory - Koppl, Roger (Emerald, 2005)
The contributors to this volume seriously engage issues in the crossroads where biology, psychology, and economics meet. The volume makes several important contributions to the area and provides an overview of the current state of knowledge. Biologist David Sloan Wilson, psychologists Robert Kurzban and C.A. Aktipis, economists Geoffrey Hodgson, Paul Rubin and Evelyn Gick, and jurist David Friedman consider altruism, selfishness, group selection, methodological individualism, dominance hierarchies, and other issues relating evolutionary psychology to economics. Several contributors, such as Viktor Vanberg and Brian Loasby, pay special attention to the role of F. A. Hayek and other Austrian thinkers in shaping evolutionary approaches to economic theory.Theoretical biologist Deby Cassill relates her revolutionary theory of skew selection in biology to perennial issues in political economy. The volume includes a symposium on group selection and methodological individualism. In an important paper, D. G. Whitman argues that group selection and methodological individualism are compatible and complementary. Comments from Elliot Sober & David Sloan Wilson, Richard Langlois, Todd Zywicki, and Adam Gifford offer a heterogeneous set of responses to Whitman's argument. Roger Koppl's introduction constitutes a review essay and includes an argument that Austrian economists have a comparative advantage in bringing the Verstehen tradition of social thought into contact with recent work in biology and evolutionary psychology.
Keywords: Economic theory.; elektronické knihy; electronic books